Ressocialização: um pacto frágil: estudo indutivo no complexo PPP de Ribeirão das Neves - Guéguen, Chloé Roselyne Joséphine (2017)
The following work relates the experience of an inductive research dealing with a special prison world, the first unit of the Prison Complex of Ribeirão das Neves in Minas Gerais (Brazil). Based on the Appreciative Inquiry method, group dynamics were organised and conceived as encounters between inmates and the prison staff. Starting from these meetings, week after week and along the interactions, the study set its purpose: to find out what are the goals and other benchmark standards to behave into the prison. Then, thanks to the data analysis, the issue about the prisoners rehabilitation (ressocialização in portuguese) was highlighted as the most relevant one. What appeared central to the discussions was the use of this expression as a keyword by the prison unity so that this one could implement the legitimacy of its action. Nevertheless, since the end of the empirical activities, it has been appointed that the meaning of this word as a goal for the prison in question has not been discovered yet. Therefore, in the frame of this research, the notion of rehabilitation in jail is going to be explored and discussed factually, that is to say, by the people who are experiencing the daily life in this place. Indeed, rather than a guide for action concerning everybody in the unity, rehabilitation has been understood more as language convention between the different profiles of persons. This way, as a deal, it may enable the prevention of open conflicts into the institution in question.